Frugivore diversity increases evenness in the seed rain on deforested tropical landscapes - Camargo, Paulo H. S. A. [UNESP]; Carlo, Tomás A.; Brancalion, Pedro H. S.; Pizo, Marco A. [UNESP] (Wiley, 2022)
The diversity of tropical forests is strongly shaped by mutualistic interactions involving plants and frugivores that disperse their seeds. However, it is little known how decreases in the diversity of frugivores can affect seed dispersal patterns, plant community composition and species' coexistence in tropical forest landscapes. Here, we investigated the effects of bird frugivore diversity on seed dispersal of rare plant species and on the magnitude of equalizing effects on the seed rain in open areas within 12 fragmented landscapes in the Brazilian Atlantic Forest. We monitored the production of bird-dispersed seeds and bird abundance in forest fragments, and sampled the seed rain and the activity of birds attracted to experimental tree nuclei established in neighboring pastures. The activity of frugivores in tree nuclei was positively correlated with the diversity of birds recorded in nearby forest fragments, and the seed rain diversity increased with frugivore activity. The proportion of seeds dispersed more frequently than expected by chance in tree nuclei increased linearly with the species' richness of birds. The richness and abundance of active frugivores in deforested areas promoted a seed rain with evenness and diversity up to five times greater than the seed pool available in forest fragments due to the proportional increase in the dispersal of rare plant species and a concomitant proportional decrease in the dispersal of dominant fruiting plants. Furthermore, every additional bird species detected in a site was associated with a 10% increase in the equalizing effect on dispersed seeds' relative abundance. Our results show that the aggregated behavior of avian frugivore communities on deforested areas results in higher species richness in the seed rain of plant communities and underscore the urgency to reduce bird species' loss and the simplification of their communities in tropical landscapes.